2020
DOI: 10.3389/fonc.2020.584733
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Nomogram Model Based on mRNA Expression of DNA Methylation-Driven Genes for Gastric Cancer

Abstract: PurposeThe exploration and interpretation of DNA methylation-driven genes might contribute to molecular classification, prognostic prediction and therapeutic choice. In this study, we built a prognostic risk model via integrating analysis of the transcriptome and methylation profile for patients with gastric cancer (GC).MethodsThe mRNA expression profiles, DNA methylation profiles and corresponding clinicopathological information of 415 GC patients were downloaded from The Cancer Genome Atlas (TCGA). Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…The AUC of this radiogenomic nomogram is 0.838 in the training cohort and 0.791 in the validation cohort, which is higher than the previously published genomic nomogram (AUC = 0.744) by Chen et al. ( 35 ) and radiomic nomogram (AUC = 0.771) by Wang et al. ( 36 ).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The AUC of this radiogenomic nomogram is 0.838 in the training cohort and 0.791 in the validation cohort, which is higher than the previously published genomic nomogram (AUC = 0.744) by Chen et al. ( 35 ) and radiomic nomogram (AUC = 0.771) by Wang et al. ( 36 ).…”
Section: Discussioncontrasting
confidence: 61%
“…In the nomogram, RIS, tumor metastasis, lymph node positive detection rate, primary tumor, and age were kept after multivariate Cox analysis. The AUC of this radiogenomic nomogram is 0.838 in the training cohort and 0.791 in the validation cohort, which is higher than the previously published genomic nomogram (AUC = 0.744) by Chen et al (35) and radiomic nomogram (AUC = 0.771) by Wang et al (36). In addition, combining radiogenomic, clinical, and pathological information together produced this nomogram with better performance than using TNM staging information alone (Figure 4F).…”
Section: Discussionmentioning
confidence: 58%
“…Liu et al have identified GAMT as a biomarker of prognosis in patients with advanced GC treated with docetaxel, cisplatin, and S-1 (DCS) [50]. Chen et al also have demonstrated that high expression of GAMT, a gene driven by DNA methylation, was remarkably associated with poor prognosis [51].…”
Section: Discussionmentioning
confidence: 99%
“…GNAI1 (G protein subunit alpha i1) is a member of the Gαi family and functions to suppress adenylate cyclase activity. To date, only a handful of studies have shown that the high expression and low DNA hypermethylation of GNAI1 were significantly associated with poor prognosis in GC [33].…”
Section: Discussionmentioning
confidence: 99%